Peran Guru Akidah Akhlak dalam Membina Akhlakul Karimah Peserta Didik di MA Darul Amin Palangka Raya - Khairul Sadi; Zainap Hartati; Abdullah Abdullah (Kamaya: Jurnal Ilmu Agama, 2025)
Fostering good morals is an important part of madrasa education, but at MA Darul Amin Palangka Raya, students are still found to lack discipline and lack polite behavior. This study aims to describe the role of Akidah Akhlak teachers in fostering good morals in students and to identify strategies, supporting factors, and inhibiting factors. This study uses a qualitative approach with a case study method. Data were obtained through observations of learning and religious activities, interviews with Akidah Akhlak teachers, the madrasah principal, the deputy head of curriculum, and students, as well as supporting documentation. The results show that Akidah Akhlak teachers play a role through role models, positive behavioral habits, educational reprimands, and a personal approach. Teachers also actively guide students in religious activities such as tadarus, dhuha prayer, and religious studies so that moral values ​​are more easily internalized. Supporting factors for fostering come from a religious madrasah environment, scheduled religious programs, and leadership support. Inhibiting factors include external environmental influences and unstable student discipline. This study concludes that the development of noble morals will be effective if exemplary behavior and religious activities are carried out consistently and supported by a conducive madrasa environment.